Penguatan Kesadaran Hukum Ibu-Ibu Pengajian dalam Pencegahan Bullying pada Anak melalui Literasi Keluarga - Atmari; Ahmad Fausi; Margo Utomo; Yovi Dwi Oktaviani; Bilqisthi Ari Putra (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Bullying among children remains a persistent social issue within family and educational environments, with significant impacts on children’s psychological development. This community service program aims to enhance the legal awareness of women’s religious study groups in preventing bullying among children through family-based legal literacy. The method used is a qualitative descriptive approach with a community-based participatory strategy, implemented through legal education, interactive discussions, and case studies within the religious study forum. The results indicate an improvement in participants’ understanding of the concept of bullying, its forms, and its impacts on children. Furthermore, there was a noticeable shift in attitudes, from perceiving bullying as mere childhood misbehavior to recognizing it as a serious issue that must be prevented early through family involvement. Participants also showed increased engagement during the activities, reflected in active discussions and reflections on parenting experiences. This program concludes that religious study groups can serve as an effective medium for strengthening family legal literacy, particularly in efforts to prevent bullying among children through the active role of mothers as primary agents within the family environment.